Neuropharmacological properties of the cathinones - Shortall, S.E. (2015)
At the height of its popularity, mephedrone was the most common recreationally used cathinone. This is thought to be due to its perceived likeness to MDMA. Therefore the aim of this thesis was to examine mephedrone-induced changes in behaviour, body temperature or neurochemistry in the rat and to compare these changes to those observed following MDMA administration. This was achieved by assessing changes in body temperature following acute mephedrone, MDMA, cathinone or methcathinone administration. Additionally, locomotor activity and cognitive tasks were performed following chronic intermittent administration of mephedrone, MDMA or cathinone. These behaviours, as well as mephedrone-induced changes to body temperature and ‘anxiety-related’ behaviour, were also assessed following either pre-treatment with MDMA or co-administration of caffeine. Finally, locomotor activity, body temperature changes and in vivo striatal dopamine release were assessed following rapid repeated dosing of mephedrone, and the roles of dopamine, 5-HT and noradrenaline in these responses were examined. Post mortem monoamine concentrations from specific brain regions were also assessed following acute, chronic intermittent and rapid repeated dosing of mephedrone.